COMPETITIVENESS OF MALAYSIAN EXPORT - Yean, Tham Siew (Penerbit USM, 2001)
Malaysia's move toward export-promotion can be traced back to the late sixties with the enactment of the Investment Incentive Act in 1968. This shift was prompted by both the practical reality of a small dorriestic market, domestic unemployment, as well as the general perception that higher exports are positively related to a higher growth of the Gross Domestic Product (GDP).